Alternative usage of initiation codons in mRNA encoding the cAMP-responsive-element modulator generates regulators with opposite functions. - Delmas, V (1992)
The cAMP-responsive-element modulator (CREM) gene encodes both antagonists (CREM alpha/beta/gamma) and an activator (CREM tau) of cAMP-responsive transcription by alternative splicing. In adult mouse brain a predominant 21-kDa protein, not corresponding to any previously characterized transcript, is detected with specific CREM antibodies. A developmental switch occurs in brain as expression changes at birth from CREM alpha/beta to the 21-kDa protein. We show that the 21-kDa protein corresponds to S-CREM (short CREM), a protein produced by the use of an internal AUG initiation codon in the CREM tau transcript. S-CREM shares with the other CREM proteins the basic DNA-binding and leucine-zipper dimerization domain. S-CREM functions as a transcriptional repressor of cAMP-induced transcription. Thus, two proteins with opposite functions are generated by alternative translation using two AUG codons within the same reading frame.